2001
DOI: 10.1155/dte.7.165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rectal Varices by Endoscopic Ultrasonography in Patients With Portal Hypertension

Abstract: The usefulness of endoscopic ultrasonography (EUS) in the evaluation of rectal varices (RV) was determined in 50 patients with portal hypertension (PH) and 25 PH-free controls. F1 and F2 varices and angiectasia were specific for the PH group as evaluated by endoscopy, but there was no difference between the PH and the control groups with respect to the frequency of blue vein. The detection rate of submucosal veins (SMV) with EUS was 88% for the PH group and 68% for the control group. The mean SMV diameter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…We found the prevalence of these features within the ranges already reported in the literature. For example, the prevalence of blue veins in our study was 38% as compared with 36% found by Kobayashi (6).…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…We found the prevalence of these features within the ranges already reported in the literature. For example, the prevalence of blue veins in our study was 38% as compared with 36% found by Kobayashi (6).…”
Section: Discussioncontrasting
confidence: 64%
“…Colonic changes in cirrhosis have been investigated in numerous studies. They were described by many terms that included vascular ectasias, vascular lesions, colitis‐like abnormalities, red spots, dendriform vasodilatations, angiodysplastic‐like lesions, redness, blue veins, spider angiomas, hyperaemia and varices (3, 5, 6, 8, 9). Considering this plethora of terms, not surprisingly, the prevalence of portal hypertensive colopathy has been reported to occur between 17 and 70% of patients, with portal hypertension and normal colon described between 9 and 42% of cirrhotics (1, 10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As portal hypertension tends to persist, it seemed logical to offer partial therapy for EIE-RVs. 17,18 This case also shows that rectogenital communication exists in portal hypertension and represents dilatation of preexisting embryonic vascular channels. 19,20 In the available literature, only one case report of major bleeding from EIE-RVs has been described that was managed by RIP.…”
Section: Discussionmentioning
confidence: 67%